IMPELEMENTASI BAHAN AJAR BERMODELKAN ADVANCE ORGANIZER PADA PEMBELAJARAN AKTIF DI KELAS XI SMA NEGERI 7 PADANG - Dian Mayasari (Universitas Negeri Padang, 2014)
Learning physics in high school show not optimal results,this is caused by several factors, including student learning has not been able to connect the old with the new learning, and also teaching materials used are less variable and can not connect old learning with new learning, so that students the difficulties in understand learning physics. The application of learning materials is modeled Advance Organizer can be used as a solution in solving the problem, learning materials which can increase the variety of learning materials, while Advance Organizer is a learning model that can connect the old with the new learning. Research type is Quasi experiment, the design of Randomized Control Group Design Only, while the sample came from the students of class XI Science SMAN 7 Padang, with purposive sampling technique sampling. The data of this study consists of cognitive, affective, and psychomotor domains. The data were then analyzed using the t test. The results showed that the working hypothesis that there is a significant effect of the implementation of learning materials are modeled Advance Oraganizer on active learning in class XI Science SMAN 7 Padang accepted level of 95%.